ANALISIS IMPLEMENTASI PERATURAN PRESIDEN NOMOR 65 TAHUN 2006 DALAM PEMBANGUNAN DOUBLE TRACK DI KELURAHAN WULUNG KECAMATAN RANDUBLATUNG KABUPATEN BLORA - Priandhini, Firda; Astuti, Puji; Manar, Dzunuwanuz Ghulam (Journal of Politic and Government Studies, 2014)
Construction of double track railway lines will give some positive impact , both positive for national transport and have a positive impact on the national economy. In this study focused writing to see the implementation process of land acquisition or construction of double track railway lines in the Village District of Randublatung Wulung Blora pursuant to Presidential Decree No. 65 Year 2006 on Land Procurement for Development Implementation for Public Interest . Method used in this study is a qualitative research method . The results shows that the implementation of land acquisition in accordance with the provisions of the double rail Presidential Regulation No. 65 Year 2006 on Land Procurement for Development Implementation for Public Interest which there are several stages , but in practice there are several obstacles .Keywords : Land Acquisition , Policy Analysis